Gaming Green: The Educational Potential of Eco – A Digital Simulated Ecosystem - Fjællingsdal, Kristoffer S.; Klöckner, Christian A. (Frontiers in Psychology, 2019)
Research into the use of videogames in education is on the rise, and they are cementing their position as part of the modernized, digital classroom. Sustainability education has also become a subject of interest among environmentally minded game developers and understanding the educational impact of such games is rapidly becoming an important field. This study examined the educational potential of the digital simulated ecosystem known as Eco, in order to reveal how playing Eco might promote environmental literacy and consciousness surrounding ecosystems. Qualitative data from 7 respondents were subjected to a thematic analysis, revealing two main themes that highlight both game-based learning outcomes as well as barriers against learning. The findings indicate that Eco is a viable tool for promoting environmental literacy about ecosystems, and suggestions for future implementation of Eco are provided.